OP58 Associations between parental vaping and youth smoking and vaping in the UK: cross-sectional survey findings. (September 2018) - Green, MJ; Gray, L; Sweeting, H; Benzeval, M
Abstract : Background: E-cigarette use has been rising steadily in the UK since 2011. Mounting evidence suggests e-cigarette use ('vaping') is safer than traditional cigarettes ('smoking'), and can aid smoking cessation. Nevertheless concerns are still raised that vaping may re-normalise smoking behaviour and help introduce youth to traditional cigarettes. Parental smoking is long-established as a risk factor for youth smoking, so parental vaping may be an important component of any normalisation effects of e-cigarettes on youth. We estimated associations of parental vaping with youth smoking and vaping. Methods: Data were from the 7th wave of the Understanding Society study, a representative annual panel study of UK households. Youth and parents self-reported current vaping and current and past smoking (parental vaping/smoking coded for any use in couples). Logistic regression analyses were conducted in STATA on 2373 youth aged 10–15 with valid data (65% of 3635 interviewed; 51% female). Models were weighted for study non-response and adjusted for potential confounders (gender, age, UK country, ethnic minority, single parent status, parental education, occupation, income and parental smoking). Where there were interactions between parental vaping and parental smoking (never, ex or current), we estimated ORs within strata of parental smoking. With responses from previous surveys we additionally examined current smoking in youth who had never smoked before (n=2, 243; i.e. initiation of smoking). Results: Vaping and smoking were rare among youth (3.5% and 2.3% respectively) but more youth had parents who vaped (11.6%) or were ex (39.7%) or current (24.9%) smokers. Parental vaping was not clearly associated with youth vaping after adjustment for confounders (OR: 1.86; 95% CI 0.70 to 4.96). However, associations between parent and youth vaping varied by parental smoking (p-value for interaction: 0.043) being strongest among youth whose parents were ex-smokers (OR: 4.99; 95% CI 0.94 to 26.53). After adjustment, parental vaping was not clearly associated with youth current smoking either (OR: 1.26; 95% CI 0.38 to 4.19), which held across strata of parental smoking (interaction p-value: 0.102). However, parental vaping was associated with youth smoking initiation, even after adjustment (OR: 4.63; 95% CI 1.29 to 16.58), and this too did not vary by parental smoking status (interaction p-value: 0.115). Conclusion: There was not strong evidence that parental vaping encouraged youth smoking or vaping overall. However, some indications of increased risk (e.g. for smoking initiation, or among youth whose parents were ex-smokers) warrant further study and monitoring to further inform regulation, especially as increasing numbers of smokers (including parents) switch to e-cigarettes.